Thoracoscopic Patch Repair of Congenital Diaphragmatic Hernia in a Neonate Using Spiral Tacks: A Case Report - Riquelme, Mario A; Guajardo, Carlos D; Juarez-Parra, Marco A; Elizondo, Rodolfo A; Cortinas, Julio C (Journal of Neonatal Surgery, 2016)
Please see fulltext